2012
DOI: 10.1111/j.1600-0633.2012.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of forest cover and mesohabitat types on functional and taxonomic diversity of fish communities in Neotropical lowland streams

Abstract: –  In this study, we investigated how taxonomic and functional diversity of fish communities is influenced by forest cover and mesohabitat types in Neotropical lowland streams. We sampled fish fauna of 126 five‐metre‐long mesohabitats using an electrofishing unit in forested (n = 3) and deforested (n = 3) streams in the upper Paraná River basin, south‐eastern Brazil. According to velocity and depth, three mesohabitat types have been considered: riffles (shallow and fast‐flowing habitat), pools (deep and slow‐f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
89
3
19

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 64 publications
5
89
3
19
Order By: Relevance
“…However, other studies focusing on other species of Imparfi nis, as well as I. schubarti, have confi rmed the results reported here (Ferreira & CasaTTi, 2006;silva et al, 2012). In contrast to the patterns observed for P. taenioptera, the less variable and strictly insectivorous diet exhibited by the studied riffle-dwelling species corroborates previous findings that have highlighted the dominance of insectivorous species with more specialized habitats in riffles (CasaTTi & CasTro, 1998;Teresa & CasaTTi, 2012). The fast water velocity and the limited availability of food items present in riffles (anGermeier & sChlosser, 1989) are restrictive conditions which, according to Teresa & CasaTTi (2012), are successfully explored by two dominant functional groups: benthicgrazers-periphytivorous species, as represented mainly by loricariid species, and benthic-speculators-insectivorous fish, as represented by heptapterid species.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…However, other studies focusing on other species of Imparfi nis, as well as I. schubarti, have confi rmed the results reported here (Ferreira & CasaTTi, 2006;silva et al, 2012). In contrast to the patterns observed for P. taenioptera, the less variable and strictly insectivorous diet exhibited by the studied riffle-dwelling species corroborates previous findings that have highlighted the dominance of insectivorous species with more specialized habitats in riffles (CasaTTi & CasTro, 1998;Teresa & CasaTTi, 2012). The fast water velocity and the limited availability of food items present in riffles (anGermeier & sChlosser, 1989) are restrictive conditions which, according to Teresa & CasaTTi (2012), are successfully explored by two dominant functional groups: benthicgrazers-periphytivorous species, as represented mainly by loricariid species, and benthic-speculators-insectivorous fish, as represented by heptapterid species.…”
Section: Discussioncontrasting
confidence: 55%
“…These results are congruent with the temporally variable resources availability reported for pools (anGermeier & Karr, 1983). The opposite patterns have been suggested for riffl es, whose environmental conditions and resource availability would be less variable than found in pools (Teresa & CasaTTi, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Many studies (Bojsen and Barriga, 2002;Casatti, et al, 2012;Teresa and Casatti, 2012) have also showed the effects of riparian vegetation suppression on fish assemblage; i.e., it leads to their simplification, with a high dominance of tolerant species and loss of ecosystem services. Moreover, Casatti et al (2015) have found that although environments without riparian vegetation may have higher richness and diversity of fish, they also have a high functional redundancy, mostly related to feeding.…”
Section: Introductionmentioning
confidence: 99%